A Multimodal Analysis of Uda and Uni Selection’ Poster Advertisement in Pesisir Selatan - Rahayu, Shilfa; Irawan, Andi Muhammad (English Language and Literature, 2021)
This study discusses "A Multimodal Analysis of Uda and Uni Selection' Poster Advertisement in Pesisir Selatan" which is a talent search event poster that aims to promote tourism. Thus, to convey the message in the poster not only use visual elements but also verbal elements. The purpose of this research is to identify visual and verbal elements, as well as to describe the representation of verbal and visual elements represented in the message. This study used a qualitative descriptive method and the data sources were three posters of Uda Uni Election which were randomly selected on the internet. This analysis focused on Halliday's (2004) ideational function to analyze verbal texts,  Kress' and van Leeuwen's (2006) representations to analyze visual texts, and Cheong's (2004) theory to identify the structure of poster advertisements. The results of the analysis show that the most common verbal elements used in posters were announcements and the most common visual elements in posters were emblems. The verbal elements are often represented by the material process, while the visual elements are represented by the Action process and Reactional Process.